Pengaruh Politik Kekuasaan Terhadap Pengembangan Pendidikan Islam di Era Safawi dan Mughal - Ahmad Rifai; Irhamni Sabil Abdillah; Aqilatun Arum; Siti Alifah Ailatun Nasuha; Faiz Fikri Al Fahmi (IAI Nasional Laa Roiba Bogor, 2025)
The golden age of the Syafavid and Mughal empires was the main highlight of Islamic civilization, where the political success of the kingdoms also influenced the progress of Islamic education. Islamic education has an important role in maintaining and developing the Islamic identity of a civilization. During the Safavid kingdom, Islamic civilization reached its peak in the fields of art, literature and architecture. The influence of power politics plays a key role in supporting the development of Islamic education by building advanced educational institutions centered on Islamic teachings. Islamic education at that time provided a strong foundation for the intellectuality of Muslims. Meanwhile, the period of Mughal rule also showed the glory of Islamic civilization. Islamic education under Mughal rule experienced significant development, where classical books were translated into local languages to increase access to education for the wider community. Mughal political power gave great impetus to the spread of Islamic science and religion.